A sodium-ion battery
Patent Information
- Application Number
- CN202510548463.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]针对以上技术问题,本发明提供了一种钠离子电池,来克服现有钠离子电池电解液分解产气影响电池循环性能和安全性能的技术问题
[0056]本发明的钠离子电池,采用碳酸乙烯亚乙酯和硫酸乙烯酯做添加剂,在电极材料表面形成稳定致密的SEI膜,抑制电解液分解、降低产气;并限定碳酸乙烯亚乙酯的含量a、硫酸乙烯酯的含量b、负极活性材料的比表面积c、正极活性材料的碱度d之间的关系满足0.3≤10(a+b)/(c+d)≤8,可有效抑制钠离子电池的产气现象,达到改善钠离子电池的循环性能和安全性能的目的。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical technology, and more particularly to a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries are similar in principle and structure to lithium-ion batteries, utilizing an electrolyte medium that conducts alkali metal ions to allow reversible shuttle transport of these ions between two electrodes. Compared to lithium-ion batteries, sodium-ion batteries are more readily available, have lower and less fluctuating costs, and possess a wide temperature range and high safety, making them a potential alternative. With continuous advancements in sodium-ion battery technology, they are poised to occupy an important place in my country's energy system and are one of the key new battery technologies supported by national policy.
[0003] In the current development of sodium-ion batteries, the problem of electrolyte decomposition leading to battery gas production cannot be ignored, as it seriously affects the cycle performance and safety performance of sodium-ion batteries. Summary of the Invention
[0004] To address the above technical problems, this invention provides a sodium-ion battery that overcomes the technical issue of electrolyte decomposition and gas generation affecting battery cycle performance and safety performance in existing sodium-ion batteries.
[0005] The present invention adopts the following technical solution:
[0006] A sodium-ion battery includes a positive electrode, a negative electrode, and a non-aqueous electrolyte;
[0007] The positive electrode includes a positive electrode material layer containing a positive electrode active material, and the negative electrode includes a negative electrode material layer containing a negative electrode active material, wherein the negative electrode active material is selected from one or more of hard carbon and soft carbon;
[0008] The non-aqueous electrolyte includes sodium salt, solvent, and additives, wherein the additives include ethylene carbonate and ethylene sulfate.
[0009] The sodium-ion battery meets the following conditions:
[0010] 0.3≤10(a+b) / (c+d)≤8, 0.5≤a≤4, 0.1≤b≤4, 2≤c≤8, 8≤d≤12;
[0011] Where: a represents the mass percentage of ethylene carbonate in the non-aqueous electrolyte, in wt%;
[0012] b represents the mass percentage of vinyl sulfate in the non-aqueous electrolyte, in wt%;
[0013] c represents the specific surface area of the negative electrode active material in the negative electrode material layer, in m². 2 / g;
[0014] d represents the alkalinity of the positive electrode active material in the positive electrode material layer.
[0015] The sodium-ion battery of this invention uses ethylene ethylene carbonate and ethylene sulfate as additives, and limits the relationship between the content of ethylene ethylene carbonate (a), the content of ethylene sulfate (b), the specific surface area of the negative electrode active material (c), and the alkalinity of the positive electrode active material (d) to satisfy 0.3 ≤ 10(a+b) / (c+d) ≤ 8. This effectively suppresses gas generation in sodium-ion batteries, overcomes the disadvantage of low initial efficiency of negative electrode materials, and achieves the goal of improving the cycle performance and safety performance of sodium-ion batteries. If 10(a+b) / (c+d) < 0.3, ethylene ethylene carbonate cannot effectively participate in film formation, resulting in poor film formation and poor negative electrode interface stability, which exacerbates side reactions, causes significant gas generation, and degrades battery performance. If 10(a+b) / (c+d) > 8, the electrolyte components decompose excessively to form a film, and the battery impedance will increase significantly, resulting in severe degradation of cycle performance. Preferably, the content relationship of a, b, c, and d is 1 ≤ 10(a+b) / (c+d) ≤ 6.
[0016] In this invention, ethylene ethylene carbonate and vinyl sulfate are combined as electrolyte additives. When ethylene ethylene carbonate is used in sodium-ion batteries, it decomposes earlier than the electrolyte components during charging and discharging, forming a stable and dense SEI film on the electrode material surface. This effectively prevents solvent molecules and solvated sodium ions from co-embedding into the negative electrode, minimizing the degree of electrolyte decomposition and thus improving the charge-discharge efficiency and cycle characteristics of the sodium-ion battery. Simultaneously, the use of vinyl sulfate improves the SEI film composition in sodium-ion batteries, thereby improving the high-temperature performance of the batteries, suppressing initial capacity loss, and enhancing cycle capability.
[0017] Specifically, the content 'a' of ethylene ethylene carbonate is 0.5~4 wt%. If the content of ethylene ethylene carbonate is less than 0.5 wt%, it cannot effectively participate in film formation, resulting in poor film quality, which in turn leads to poor stability of the positive and negative electrode interfaces, aggravated side reactions, significantly increased gas production, and deterioration of battery performance. If the content of ethylene ethylene carbonate is greater than 4 wt%, it will excessively participate in film formation, leading to a significant increase in impedance, which in turn leads to severe degradation of cycle performance. Specifically, in some embodiments of the present invention, the content 'a' of ethylene ethylene carbonate is 0.5 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.5 wt%, 1.8 wt%, 2 wt%, 2.4 wt%, 2.5 wt%, 2.7 wt%, 3 wt%, 3.2 wt%, 3.5 wt%, 3.8 wt%, or 4 wt%; preferably, the content 'a' of ethylene ethylene carbonate is 1~3 wt%.
[0018] Specifically, the content of vinyl sulfate b is 0.1~4wt%. If the content of vinyl sulfate is less than 0.1wt%, the SEI film quality is poor, causing ethylene carbonate to fail to stably exert its gas-suppressing effect. If the content of vinyl sulfate is greater than 4wt%, the excessive vinyl sulfate leads to over-film formation, resulting in increased battery impedance and thus degrading battery performance. Specifically, in some embodiments of the present invention, the content of vinyl sulfate b is 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.5wt%, 2.7wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.6wt%, 3.8wt%, or 4wt%; preferably, the content of vinyl sulfate b is 0.6~3wt%.
[0019] In this invention, the specific surface area c of the negative electrode active material in the negative electrode material layer is limited to 2~8m². 2 / g, which helps ethylene carbonate participate in the formation of a stable solid electrolyte membrane, suppresses battery gas production, and enables sodium-ion batteries to exhibit ideal kinetic performance and initial coulombic efficiency. If the specific surface area c of the negative electrode active material in the negative electrode material layer is less than 2m², 2 At a concentration of / g, there are fewer migration channels for sodium ions, resulting in poor SEI film formation and preventing ethylene carbonate from achieving its optimal effect; if the specific surface area c of the negative electrode active material in the negative electrode material layer is greater than 8m², ... 2 / g, the increased SEI film area leads to uneven film formation of ethylene carbonate and poor gas generation suppression. Specifically, in some embodiments of the present invention, the specific surface area c of the negative electrode active material is 2m². 2 / g, 2.5m 2 / g、3m 2 / g, 3.5m 2 / g、4m 2 / g, 4.5m 2 / g、5m 2 / g, 5.5m 2 / g、6m 2 / g, 6.5m 2 / g、7m 2 / g, 7.5m 2 / g、8m 2 / g; Preferably, the specific surface area c of the negative electrode active material in the negative electrode material layer is 2~6m². 2 / g.
[0020] In this invention, the alkalinity d of the positive electrode active material in the positive electrode material layer is limited to 8-12. Through multiple experiments, the inventors have found that batteries within this alkalinity range have controlled residual alkali on the positive electrode surface, suppressing the generation of CO, CO2, O2, and other substances during the electrochemical reaction, thus improving battery safety. If the alkalinity d of the positive electrode active material in the positive electrode material layer is greater than 12, the residual alkali on the positive electrode surface is too strong, easily triggering a gas-generating reaction to produce carbon dioxide; washing with water can reduce the alkalinity of the positive electrode active material. Specifically, in some embodiments of this invention, the alkalinity d of the positive electrode active material in the positive electrode material layer is 8, 8.4, 8.5, 8.7, 9, 9.1, 9.3, 9.5, 9.8, 10, 1.02, 10.5, 10.8, 11, 11.5, or 12; preferably, the alkalinity d of the positive electrode active material in the positive electrode material layer is 8-10.
[0021] Specifically, the alkalinity testing method for the positive electrode active material in this invention is as follows:
[0022] ① Prepare 1g of the electrode material to be tested and add 20g of pure water;
[0023] ② Stir on a magnetic stirrer for 30 minutes to fully disperse it in pure water;
[0024] ③ Measure the pH value at 25℃.
[0025] Precautions:
[0026] ① When adding pure water, be careful to control the flow rate to avoid causing the electrode material to scatter;
[0027] ② To ensure even mixing, shake again for 1 minute before testing the pH value;
[0028] ③ A control electrode material and pure water should be provided for easy comparison;
[0029] ④ Before measuring the pH value, ensure that the pH meter is in the calibration state. The pH value in the state liquid at room temperature is 6.84.
[0030] ⑤ To ensure accurate measurement, the pH value should be tested three times and the average value should be taken.
[0031] Specifically, as some embodiments of the present invention, the additive further includes one or more of the following: cyclic carbonate compounds other than ethylene carbonate, fluorinated cyclic carbonate compounds, cyclic sulfonates, cyclic sulfates other than vinyl sulfate, phosphate compounds, and nitrile compounds;
[0032] Preferably, the cyclic carbonate compound is selected from one or more of vinylene carbonate and ethylene methylene carbonate;
[0033] The fluorocyclic carbonate compounds are selected from one or more of fluoroethylene carbonate and difluoroethylene carbonate.
[0034] The cyclic sulfonate compounds are selected from one or more of 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, and propenyl-1,3-sulfonyl lactone.
[0035] The cyclic sulfate compound is selected from one or more of 4-methyl vinyl sulfate and propylene sulfate;
[0036] The phosphate ester compound is selected from one or more of triargyl phosphate, trimethyl phosphate, triethyl phosphate, and tris(trimethylsilane) phosphate;
[0037] The nitrile compounds are selected from one or more of succinic anionibacterium, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrionitrile, adiponitrile, heptanonitrile, octanilide, nonadionitrile, and sebaconitil.
[0038] Specifically, as some embodiments of the present invention, the additive has a mass percentage content of 0.01~10wt% based on the total mass of the non-aqueous electrolyte being 100%.
[0039] Specifically, as some embodiments of the present invention, the solvent includes at least one of carbonates, carboxylic acid esters, and ethers;
[0040] Preferably, the carbonates include C3-C5 cyclic or chain carbonates; the cyclic carbonate solvents include one or more of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonate solvents include one or more of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC).
[0041] Preferably, the carboxylic acid esters include C2-C6 carboxylic acid esters, and the solvent for the C2-C6 carboxylic acid esters is selected from one or more of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and propyl propionate.
[0042] Preferably, the ether solvent comprises C4-C10 cyclic ethers or chain ethers, wherein the cyclic ether is selected from one or more of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; and the chain ether is selected from one or more of dimethoxymethane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, ethylene glycol diethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0043] Specifically, as some embodiments of the present invention, the sodium salt includes one or more of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium bis(fluorosulfonyl)imide (Na[(FSO2)2N]) or sodium bis(trifluoromethanesulfonyl)imide (Na[(CF3SO2)2N]).
[0044] Specifically, as some embodiments of the present invention, the negative electrode further includes a negative electrode conductive agent, which is selected from one or more of acetylene black, Super P, graphene, Ketjen black, SFG-6, carbon nanotubes, and graphyne.
[0045] Specifically, as some embodiments of the present invention, the negative electrode further includes a negative electrode binder, which is selected from one or more of the following: polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluorinated vinylidene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, polyethylene, and polypropylene; acrylic resins; and styrene-butadiene rubber.
[0046] Specifically, as some embodiments of the present invention, the positive electrode active material is selected from one or more of layered transition metal oxides, Prussian compounds, and phosphate compounds.
[0047] Specifically, in some embodiments of the present invention, the chemical formula of the layered transition metal oxide is Na. x M y O z 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, M is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V; the transition metal oxide is NaNi. m Fe n Mn p O2 (m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1), NaNi m Co n Mn p O2 (m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1); more specifically, the layered transition metal oxide is selected from Na[Cu] 1 / 9 Ni2 / 9Fe 1 / 3 Mn 1 / 3 O2, Na 0.44 MnO2, NaNi 0.3 Mn 0.3 Fe 0.4 O2, Na 2 / 3 [Fe 1 / 2 Mn 1 / 2 O2, Na[Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, Na 7 / 9 [Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, NaNi 0.7 Co 0.15 Mn 0.15 O2, or one or more of the above substances.
[0048] In some embodiments of the present invention, the molecular formula of the Prussian blue analogue compound is Na x M[M′(CN)6] y ·zH2O, where M is a transition metal, M′ is a transition metal, 0<x≤2, 0<y≤1, 0<z≤20; the Prussian blue analogue compound is Na x Mn[Fe(CN)6] y ·zH2O (0<x≤2, 0<y≤1, 0<z≤20), and the Prussian blue analogue compound is Na x Fe[Fe(CN)6] y ·zH2O (0<x≤2, 0<y≤1, 0<z≤20).
[0049] In some embodiments of the present invention, the chemical formula of the phosphate compound is Na3(MO 1-x PO4)2F 1+2x , 0≤x≤1, and M is selected from one or more of Al, V, Ge, Fe and Ga; the chemical formula of the phosphate compound is Na3(VPO4)2F3, Na3(VOPO4)2F.
[0050] In some embodiments of the present invention, the chemical formula of the phosphate compound is Na2MPO4F, and M is selected from one or more of Fe and Mn; the chemical formula of the phosphate compound is Na2FePO4F, Na2MnPO4F.
[0051] Specifically, as some embodiments of the present invention, the positive electrode further includes a positive electrode conductive agent and a positive electrode binder, and the positive electrode binder and the positive electrode conductive agent may be the same as the negative electrode binder and the negative electrode conductive agent respectively, which will not be repeated herein.
[0052] In some embodiments of the present invention, the sodium-ion battery further includes a separator located between the positive electrode and the negative electrode.
[0053] The diaphragm can be a conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, or an inorganic-organic composite diaphragm, including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP, and triple-layer PP / PE / PP diaphragms.
[0054] In some embodiments of the present invention, the method for preparing the sodium-ion battery is a general method for preparing secondary batteries, which involves combining the positive electrode, the separator, and the negative electrode, injecting an electrolyte, and obtaining a sodium-ion battery.
[0055] Compared with the prior art, the present invention achieves the following beneficial effects:
[0056] The sodium-ion battery of the present invention uses ethylene ethylene carbonate and ethylene sulfate as additives to form a stable and dense SEI film on the surface of the electrode material, which inhibits electrolyte decomposition and reduces gas production. Furthermore, the relationship between the content of ethylene ethylene carbonate (a), the content of ethylene sulfate (b), the specific surface area of the negative electrode active material (c), and the alkalinity (d) of the positive electrode active material is limited to 0.3≤10(a+b) / (c+d)≤8, which can effectively suppress the gas production phenomenon of sodium-ion batteries and achieve the purpose of improving the cycle performance and safety performance of sodium-ion batteries. Detailed Implementation
[0057] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0058] Examples 1-20
[0059] This embodiment provides a sodium-ion battery, which includes a positive electrode, a negative electrode, and a non-aqueous electrolyte.
[0060] (1) Preparation of non-aqueous electrolyte
[0061] The solvents propylene carbonate (PC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) were mixed in a mass ratio of 10:70:20 to obtain an organic solvent. 1 mol / L sodium hexafluorophosphate was added, and based on 100% of the total weight of the electrolyte, additives of the types and mass percentages shown in Table 1 were added.
[0062] (2) Preparation of positive electrode plate
[0063] Take the positive electrode active material NaNi according to a mass ratio of 88:9:3 0.3 Mn 0.3 Fe 0.4 O2, conductive carbon black Super-P, and binder polyvinylidene fluoride (PVDF) are mixed and then dispersed in an appropriate amount of N-methyl-2-pyrrolidone (NMP) to obtain the positive electrode slurry. The obtained slurry is uniformly coated on both sides of aluminum foil, and after drying, calendering, and vacuum drying, aluminum leads are welded on using an ultrasonic welding machine to obtain the positive electrode plate. The thickness of the electrode plate is between 120-150 μm. The alkalinity of the positive electrode active material is shown in Table 1.
[0064] (3) Preparation of negative electrode plate
[0065] Hard carbon, conductive carbon black Super-P, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed with the negative electrode active material, and the compound shown in structural formula 1 was added. They were then dispersed in an appropriate amount of deionized water to obtain a negative electrode slurry. The slurry was coated on both sides of a copper foil, dried, calendered, and vacuum dried. Nickel leads were then welded on using an ultrasonic welding machine to obtain a negative electrode plate with a thickness of 120-150 μm. The specific surface area of the negative electrode active material is shown in Table 1.
[0066] (4) Cell fabrication
[0067] A three-layer separator with a thickness of 20 μm is placed between the positive and negative plates prepared above. Then, the sandwich structure composed of the positive plate, negative plate and separator is wound up, and the wound body is flattened and placed in an aluminum foil packaging bag. It is then vacuum baked at 75°C for 48 hours to obtain the cell to be injected with electrolyte.
[0068] (5) Electrolyte injection and formation of the battery cell
[0069] In a glove box where the dew point is controlled below -40°C, the electrolyte prepared above is injected into the battery cell, vacuum sealed, and left to stand for 24 hours.
[0070] Then, the conventional formation of the battery is carried out according to the following steps: constant current charging at 0.1C for 180 minutes, constant current charging at 0.2C to 3.8V, vacuum sealing for the second time, and then further constant current charging at 0.2C to 3.95V. After being left at room temperature for 24 hours, constant current discharge at 0.2C to 1.5V is obtained to obtain a sodium-ion battery.
[0071] Comparative Examples 1-20
[0072] Comparative Examples 1-20 include most of the operating steps in the above embodiments, except that: the types and contents of the additives are calculated based on 100% of the total mass of the electrolyte; the specific surface area of the negative electrode active material and the alkalinity of the positive electrode active material are as shown in Table 1.
[0073] Table 1
[0074]
[0075] Note: SN-succinate, PS-1,3-propanesulfonyl lactone, FEC-fluoroethylene carbonate.
[0076] Performance testing
[0077] The sodium-ion batteries prepared in Examples 1-20 and Comparative Examples 1-20 were subjected to the following performance tests:
[0078] 1. Perform cyclic charge-discharge tests at 25℃ / 45℃ within a voltage range of 1.5~3.95V, and record the capacity retention rate and volume expansion rate after 200 cycles.
[0079] 2. Internal resistance growth rate: Subtract the internal resistance measurement before cycling from the internal resistance measurement after cycling, and then divide it back to the internal resistance measurement before cycling to reflect the increase and change of the battery's internal resistance before and after cycling.
[0080] (1) The test results of Examples 1-12 and Comparative Examples 5-20 are shown in Table 2.
[0081] Table 2
[0082]
[0083] As can be seen from the test results in Table 2, the sodium-ion battery of the present invention, by using ethylene carbonate and ethylene sulfate as additives and limiting the relationship between the content of ethylene carbonate (a), the content of ethylene sulfate (b), the specific surface area of the negative electrode active material (c), and the alkalinity of the positive electrode active material (d), satisfies 0.3≤10(a+b) / (c+d)≤8, can effectively suppress the gas generation phenomenon of sodium-ion batteries and achieve the purpose of improving the cycle performance and safety performance of sodium-ion batteries.
[0084] As can be seen from the test results of Examples 1-12, when the relationship between the content of ethylene carbonate (a), the content of ethylene sulfate (b), the specific surface area of the negative electrode active material (c), and the alkalinity of the positive electrode active material (d) further satisfies 1≤10(a+b) / (c+d)≤6, the sodium-ion battery exhibits better gas generation suppression effect and cycle performance.
[0085] As can be seen from the test results of Example 1 and Comparative Examples 5-8, when conventional additives are used to replace either ethylene ethylene carbonate or ethylene sulfate in sodium-ion batteries, or when only ethylene ethylene carbonate or ethylene sulfate is contained, it is impossible to simultaneously guarantee the suppression of gas generation in sodium-ion batteries and the improvement of room temperature, high temperature cycle performance and safety performance.
[0086] As can be seen from the test results of Example 1 and Comparative Examples 9-20, when any one of the following parameters—ethylene ethylene carbonate content (a), ethylene sulfate content (b), specific surface area of the negative electrode active material (c), or alkalinity of the positive electrode active material (d)—does not meet the specified range, or when the value of 10(a+b) / (c+d) is too large or too small, the goal of suppressing gas generation in sodium-ion batteries and improving their cycle performance and safety performance cannot be achieved. This indicates that the content of ethylene ethylene carbonate (a), the content of ethylene sulfate (b), the specific surface area of the negative electrode active material (c), and the alkalinity of the positive electrode active material (d) are strongly correlated in improving the performance of sodium-ion batteries.
[0087] (2) The test results of Example 1 and Examples 13-15 are shown in Table 3.
[0088] Table 3
[0089]
[0090] As can be seen from the test results of Examples 1 and 13-15, the sodium-ion battery of the present invention, using different positive electrode active materials, can improve the cycle performance and safety performance of sodium-ion batteries and suppress gas production when the contents of ethylene ethylene carbonate (a), ethylene sulfate (b), specific surface area of negative electrode active material (c), and alkalinity of positive electrode active material (d) meet the corresponding conditions. This shows that the battery system of the present invention has universality for different positive electrode active materials.
[0091] (3) The test results of Examples 1, 16-18 and Comparative Examples 1-4 are shown in Table 4.
[0092] Table 4
[0093]
[0094] As can be seen from the test results of Examples 1 and 16-18, the sodium-ion battery of the present invention, with the addition of additives such as succinate (SN), 1,3-propanesulfonate lactone (PS), and fluoroethylene carbonate (FEC) to the non-aqueous electrolyte, can further optimize the cycle performance and gas production suppression performance of the sodium-ion battery, indicating that there is a complementary effect between ethylene ethylene carbonate, ethylene sulfate and other additives.
[0095] The test results of Example 1 and Comparative Examples 1-4 show that when the non-aqueous electrolyte contains no additives or only conventional additives, the sodium-ion battery exhibits poor cycle performance at room temperature and high temperature, poor safety performance, and poor gas production suppression. This indicates that the sodium-ion battery in the system of the present invention can effectively suppress gas production by using ethylene ethylene carbonate and ethylene sulfate in the non-aqueous electrolyte, controlling the specific surface area of the negative electrode active material, and limiting the alkalinity of the positive electrode active material, thereby improving the cycle performance and safety performance of the sodium-ion battery.
[0096] The present invention has been further described above with reference to specific embodiments. However, it should be understood that the specific description herein should not be construed as limiting the nature and scope of the present invention. Various modifications made to the above embodiments by those skilled in the art after reading this specification are all within the scope of protection of the present invention.
Claims
1. A sodium-ion battery, comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, characterized in that, The positive electrode includes a positive electrode material layer containing a positive electrode active material, and the negative electrode includes a negative electrode material layer containing a negative electrode active material, wherein the negative electrode active material is selected from one or more of hard carbon and soft carbon; The non-aqueous electrolyte includes sodium salt, solvent, and additives, wherein the additives include ethylene carbonate and ethylene sulfate. The sodium-ion battery meets the following conditions: 0.3≤10(a+b) / (c+d)≤8, 0.5≤a≤4, 0.1≤b≤4, 2≤c≤8, 8≤d≤12; Where: a represents the mass percentage of ethylene carbonate in the non-aqueous electrolyte, in wt%; b represents the mass percentage of vinyl sulfate in the non-aqueous electrolyte, in wt%; c represents the specific surface area of the negative electrode active material in the negative electrode material layer, in m². 2 / g; d represents the alkalinity of the positive electrode active material in the positive electrode material layer.
2. The sodium-ion battery according to claim 1, characterized in that, The sodium-ion battery satisfies the following condition: 1≤10(a+b) / (c+d)≤6.
3. The sodium-ion battery according to claim 1, characterized in that, The mass percentage (a) of ethylene ethylene carbonate in the non-aqueous electrolyte is 1-3 wt%.
4. The sodium-ion battery according to claim 1, characterized in that, The mass percentage b of ethylene sulfate in the non-aqueous electrolyte is 0.6~3wt%.
5. The sodium-ion battery according to claim 1, characterized in that, The specific surface area c of the negative electrode active material in the negative electrode material layer is 2~6m². 2 / g.
6. The sodium-ion battery according to claim 1, characterized in that, The alkalinity d of the positive electrode active material in the positive electrode material layer is 8~10.
7. The sodium-ion battery according to claim 1, characterized in that, The additives also include one or more of the following: cyclic carbonates other than ethylene carbonate, fluorocyclic carbonates, cyclic sulfonates, cyclic sulfates other than vinyl sulfate, phosphate compounds, and nitrile compounds; and / or, The cyclic carbonate compound is selected from one or more of vinylene carbonate and methylene vinyl carbonate; and / or, The fluorocyclic carbonate compound is selected from one or more of fluoroethylene carbonate and difluoroethylene carbonate; and / or The cyclic sulfonate compound is selected from one or more of 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, and propenyl-1,3-sulfonyl lactone; and / or, The cyclic sulfate compound is selected from one or more of 4-methylvinyl sulfate and propylene sulfate; and / or, The phosphate ester compound is selected from one or more of triargyl phosphate, trimethyl phosphate, triethyl phosphate, and tris(trimethylsilane) phosphate; and / or, The nitrile compounds are selected from one or more of succinic anionibacterium, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrionitrile, adiponitrile, heptanonitrile, octanilide, nonadionitrile, and sebaconitil.
8. The sodium-ion battery according to claim 1, characterized in that, The solvent includes at least one of carbonates, carboxylic esters, and ethers; and / or, The carbonates include C3-C5 cyclic or chain carbonates; The carboxylic acid esters include C2-C6 carboxylic acid esters; The ethers include cyclic ethers or chain ethers of C4 to C10.
9. The sodium-ion battery according to claim 1, characterized in that, The sodium salt includes one or more of sodium perchlorate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoroacetate, sodium tetraphenylborate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethanesulfonyl)imide.
10. The sodium-ion battery according to claim 1, characterized in that, The positive electrode active material is selected from one or more of layered transition metal oxides, Prussian compounds, and phosphate compounds; and / or, The chemical formula of the layered transition metal oxide is Na. x M y O z 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, M is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V; The chemical formula of the Prussian-like compound is Na. x M[M′(CN)6] y ·zH₂O, M is a transition metal, M′ is a transition metal, 0 <x≤2,0<y≤1,0<z≤20; The chemical formula of the phosphate compound is Na3(MO) 1-x PO4)2F 1+2x , 0≤x≤1, M is selected from one or more of Al, V, Ge, Fe, and Ga.
